An assessment of the influence of job demands on employee creativity and affective states - Asaad Alsakarneh; Abdelwahhab Allozi; Ahmad Wasfi Mohammad Albdour; Mohannad Mohammad Mosa Ebbini; Haitham M. Alzoubi; Bilal Sakarneh; Bilal Eneizan (Heritage and Sustainable Development)
Organisations have become increasingly aware of their employees’ job demands due to intense market competition. Investigating the antecedents of banking sector employees’ creativity is appropriate given the increased competitiveness of the sector, which is due to banks evolving into multi-service providers. This study aimed to determine the influence of job demands on Jordanian banking sector employees’ creativity and affective states. Furthermore, the influence and modification of organisational design on certain aspects of employee behaviour were examined to enable employees’ creativity to improve work-related performance. The hypotheses were examined using SmartPLS 4 and involved 175 Jordanian banking sector employees. The results demonstrated that job demands were positively related to employee creativity. Additionally, the results suggested that job demands positively influenced Affective states and created a conducive environment for employees’ creative thinking, where unprecedented challenges enhanced employees’ performance. The results are discussed to identify potential research directions.